Analysis of multicarrier frequency diverse array radar over time. Issue 4 (4th March 2022) - Zhao, Yingjian; Tian, Bo; Wang, Chunyang; Gong, Jian; Tan, Ming; Zhou, Changlin
Abstract: The frequency diverse array (FDA) can provide degrees of freedom in both the range and angle domains by controlling the frequency offset across adjacent elements. Nevertheless, the time‐variant problem affects the analysis and application of FDA, and there is a notable lack of research on the receivers of multicarrier FDA. In this paper, a novel perspective to understand the factor of time parameter is proposed. Furthermore, combined with the multiple input and multiple output scheme, two multicarrier FDA radar receivers are proposed to obtain the time‐invariant and dot‐shaped beampattern. Numerical simulations demonstrate the validity of theoretical results.